Pnematic Dilation in Achalasia - Maximilian Bittinger; Martin Wienbeck (Canadian Journal of Gastroenterology)
Pneumatic dilation is the most common first-line therapy for the treatment of achalasia. The aim of dilation is a controlled disruption of circular muscle fibres of the lower esophageal sphincter to reduce the functional obstruction. Several types of dilators and different dilation techniques are used, but the achieved results are similar. The mean success rate is about 80% in the short term, but some patients need redilation in the further course (particularly young patients). Best long term results are obtained if the lower esophageal sphincter pressure can be reduced below 10 mmHg. Major complications are rare after pneumatic dilation; the most serious complication is esophageal perforation, which occurs at a mean rate of about 2.5%. Considering the pros and cons of other effective forms of treatment of achalasia (esophagomyotomy and intrasphincteric injection of botulinum toxin), pneumatic dilation is still the treatment of choice in the majority of patients with achalasia.